The Impact of Hanging Ball Training Method on Volleyball Under Passing and Hands Eye Coordination - Hikmawati Hikmawati; Hartati Hartati; Meirizal Usra (AL-ISHLAH: Jurnal Pendidikan, 2023)
The hanging ball training method in a ring through a rope is one option to improve underhand passing practice and hand-eye coordination in volleyball. The choice of this method is based on the position of the hand when passing down. The purpose of this study was to determine the impact of hanging ball exercises in a circle on the results of volleyball underhand passing and eye-hand coordination in elementary school students. This study used an experimental method with the type of group pretest-posttest design. This research was conducted at Sekayu 8 Public Elementary School and started from October to November 2022. The sample of this study amounted to 22 students. The data was gathered through assessments measuring both motor skills and visual-motor coordination.   The data analysis in this study involves conducting tests to assess normality, homogeneity, variance-covariance homogeneity using the box-M matrix, multicollinearity, and hypotheses.   The study findings indicated a notable impact of doing hanging ball exercises in a circular motion on both the passing ability and hand-eye coordination of students during volleyball activities.   The findings of this study have significant consequences for teachers' comprehension in formulating diverse volleyball training methodologies, particularly aimed at enhancing lower passing capabilities and eye-hand synchronisation, so equipping students with proficient volleyball playing skills.